Developing a Model of Reading Materials Based on the 10-Muwashafat and Pancasila Student Profile - Bahri, Seful; Hartono, Rudi; Ningrum, Yusnita Sylvia (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2024)
This study addresses the critical need for character-based English reading materials tailored to the unique educational context of Integrated Islamic Junior High Schools (SMPIT). SMPIT's distinct curriculum incorporates the 10-Muwashafat character foundation, which aligns with broader national values encapsulated in the Pancasila student profile. Despite the importance of these character values, existing English reading materials often fail to adequately integrate them, posing a challenge for effective character education. This research employs a mixed-methods approach, combining Research and Development (R&D) methodology to develop a model of reading materials that integrates the 10 Muwashafat characters and the Pancasila student profile, aimed at supporting character formation in English language learning at SMPIT. Additionally, an experimental method is utilized to assess the model's effectiveness. Through the mixed-methods design, the study conducted an in-depth analysis of current learning materials to identify gaps in the integration of character values. Data were collected using interviews, observations, tests, and questionnaires, involving teachers, students, and education experts. Based on these findings, a new model of reading materials was designed, integrating both 10 Muwashafat and Pancasila values. The model underwent expert validation and field testing at SMPIT, followed by revisions to enhance its effectiveness based on the results. The results demonstrate that the developed reading materials significantly improve the integration of character education in English learning, aligning with the school's values and supporting students' holistic development. This study contributes to the field of educational material development by providing a framework for incorporating character education into language learning, addressing both religious and national educational goals.